Будова та індивідуальна анатомічна мінливість верхньої півмісяцевої часточки півкуль мозочка людини - Мар’єнко, Наталія Іванівна; Марьенко, Наталия Ивановна; Maryenko, Nataliia; Степаненко, Олександр Юрійович; Степаненко, Александр Юрьевич; Stepanenko, Oleksandr (My University, 2016)
Досліджена будова та описані 10 варіантів розгалуження білої речовини верхньої півмісяцевої часточки півкуль мозочка людини. Найчастіше зустрічаються 1, 2, 3 та 5 варіанти форми, які можна вважати анатомічним стандартом. Отримані дані можуть бути використані в якості критеріїв норми для діагностичних методів нейровізуалізації. Исследовано строение и описаны 10 вариантов ветвления белого вещества верхней полулунной дольки полушарий мозжечка человека.Чаще всего встречаются 1, 2, 3 и 5 варианты формы, которые можно считать анатомическим стандартом. Полученные данные могут быть использованы в качестве критериев нормы для диагностических методов нейровизуализации. Cerebellum has the most complex spatial configuration which is associated with the organization of the arbor vitae («Tree of Life”) – tree-like branched white matter, which is structural basis of its cortex. Morphological changes of cerebellar lobules are found in many congenital and acquired diseases of the cerebellum. In recent years, thanks to modern imaging techniques (MRI, fMRI, CT, SPECT, PET) morphological changes of the hemispheric and vermal lobules that occur in these diseases can be detected in vivo, which is essential for early and accurate diagnosis. However, criteria of imaging diagnostic methods which are based on information about normal structure of the cerebellum, do not take into account the features of individual anatomical variability, gender and age characteristics. Objective – to investigate individual variability and features of variant anatomy of the superior semilunar lobule of the human cerebellar hemispheres. Research was conducted at the Kharkiv regional bureau of forensic medicine on 100 cerebellums of people of both sexes, who died of causes unrelated to brain pathology, 20-99 years old. During the forensic autopsy the cerebellum and brain stem were separated and fixed during one month in 10% formalin solution. Parasagittal sections of cerebellar hemispheres were investigated. Superior semilunar lobule of the human cerebellar hemispheres is formed by fifth branch of central white matter of the cerebellum. This lobule has pyramidal shape; the apex of pyramid is located in medial part of the hemisphere, the basis is located in lateral part of the hemisphere. The main trunk of white matter is the basis of this lobule. Main trunk divides into 2-3 branches which forms visible surface of the lobule. The shape of the superior semilunar lobule of the human cerebellar hemispheres is quite varied. Differences of the structure of this lobule depend on the characteristics of the branching of the white matter, the number and location of the secondary branches. We described 10 variants of the shape of the superior semilunar lobule of the human cerebellar hemispheres. The most common variants are 1st, 2nd, 3rd and 5th. That variants can be used as anatomical standard of the lobule. There are different number of little secondary branches on superior and inferior surfaces of the main trunk of white matter; 1, 2 or 3 branches can be found on superior surface, 1-4 branches can be found on inferior surface of the main trunk of white matter.Described variants of the shape of the cerebellar lobules can be used as criteria standards of modern diagnostic imaging techniques for the diagnosis of various diseases of the CNS.The data can be used as the basis for creation of the atlases of serial sections of the cerebellum, which are based on features of the individual anatomical variability of the cerebellum.
Keywords: людина; мозочок; індивідуальна анатомічна мінливість; человек; мозжечок; индивидуальная анатомическая изменчивость; human; cerebellum; individual anatomical variability